Shifting frontiers of nitrogen pollution: A multi-scale assessment of long-term anthropogenic nitrogen inputs across the Yellow River basin - Jincheng Li; Zhonghua Li; Qiang Wang; Yan Chen; Xinyue Zhang; Taher Kahil; Dor Fridman (Ecological Indicators)
Understanding the spatial–temporal dynamics and socioeconomic drivers of anthropogenic nitrogen inputs is essential for effective nutrient management in large river basins. This study presents a comprehensive assessment of net anthropogenic nitrogen input (NANI) in the Yellow River Basin from 1980 to 2020. It integrates multi-source statistical data from national, provincial, and prefecture-level yearbooks within a hierarchical spatial framework that includes the full basin as well as secondary and tertiary sub-basins. The results show that the NANI increases by 108.9% over the study period, accompanied by a clear shift in spatial patterns. Nitrogen inputs grow most rapidly in historically low-input upstream areas, forming a “reverse growth” trend. Centroid trajectory analysis reveals a northwestward shift in nitrogen input hotspots, primarily driven by land use change and agricultural expansion. A segmented environmental kuznets curve (EKC) model identifies a turning point in per capita GDP (41,000–46,000 CNY), beyond which nitrogen inputs begin to decline. This turning point has already been reached in the midstream and downstream regions, while the upstream region continues to experience growth. Despite recent signs of decline in basin-wide nitrogen inputs since 2016, the persistence of ecological risks and the emergence of new pollution frontiers, especially in sensitive upstream zones, highlight the need for continued attention. These spatial and temporal analyses jointly reveal the “shifting frontiers” of nitrogen pollution, defined as inflection zones where input dynamics begin to transition—spatially, temporally, or economically. This study provides methodological innovation and practical insights for improving nitrogen governance in the Yellow River Basin.